Warm-Water Foot Soaking with Epsom Salt and Lower-Extremity Somatosensory Function after Ischemic Stroke: A Quasi-Experimental Controlled Study - Millatina; Dwight Mahaputera Marulitua Hutapea; Elis Anggeria (Talenta Publisher, 2026)
Somatosensory impairment after ischemic stroke can reduce lower-extremity sensitivity, impair balance, and increase fall risk. Evidence for warm-water foot soaking with Epsom salt remains limited. To evaluate its association with lower-extremity somatosensory function after ischemic stroke. This non-randomized quasi-experimental pretest–posttest controlled study included 66 participants allocated sequentially to an intervention group (n = 33) or usual-care control group (n = 33). Somatosensory function was assessed using the sensory domain of the Fugl-Meyer Assessment for the Lower Extremity. The intervention comprised soaking the feet in 5 L of water at 40 °C with 250 g Epsom salt for 20 minutes, three times weekly for four weeks. Wilcoxon signed-rank and Mann–Whitney U tests were used. Median scores increased from 7.00 to 8.00 in the intervention group (p < .001) and remained 7.00 in the control group (p = .157). The between-group difference was significant (p = .038; r = 0.256). The intervention was associated with modest improvement. Non-random allocation and the absence of a warm-water-only arm prevent conclusions about efficacy or a salt-specific effect. Keywords: Complementary therapy, Epsom salt, Ischemic stroke, Somatosensory function, Warm-water foot soaking